Q. 145.0( 4 Votes )

Solve each of the following quadratic equations:

6x2 + x - 12 = 0

Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 6; b = 1; c = -12


= 6. - 12 = - 72


And either of their sum or difference = b


= 1


Thus the two terms are 9 and - 8


Difference = 9 - 8 = 1


Product = 9. - 8 = - 72




3x(2x + 3)-4(2x + 3) = 0


(2x + 3)(3x-4) = 0


(2x + 3) = 0 or (3x-4) = 0


x = (-3)/2 or x = 4/3


Roots of equation are ,


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.